1999
DOI: 10.1590/s1516-14391999000300014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing variables on the pore structure of silica gels obtained with tetraethylorthosilicate

Abstract: In this work it was evaluated the influence of the type and concentration of the acid catalyst and the gelation temperature on the structure of pores of silica gels obtained with TEOS. The values of the major structural parameters related to the pores such as volume fraction of pore (VV), surface area per unit volume (SV), the average pore size (rP) and the connectivity of pores (GV), obtained in this work showed the possibility of tailoring the pore structure of silica gels by changing the processing variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
2
12
0
Order By: Relevance
“…10 to be 84 and 73 kJ/mol for monodisperse 3M particles and polydisperse NexSil5 particles, respectively. These apparent activation energies for bridging of aggregates are comparable to the values reported by Silva and Vasconcelos (1999); Wang and Zhang (2009) and Amiri et al (2011). The decrease in gelation time at high temperature was attributed to larger Brownian motion of the particles resulting in faster collisions (Metin et al 2011).…”
Section: Rheological Measurementssupporting
confidence: 84%
“…10 to be 84 and 73 kJ/mol for monodisperse 3M particles and polydisperse NexSil5 particles, respectively. These apparent activation energies for bridging of aggregates are comparable to the values reported by Silva and Vasconcelos (1999); Wang and Zhang (2009) and Amiri et al (2011). The decrease in gelation time at high temperature was attributed to larger Brownian motion of the particles resulting in faster collisions (Metin et al 2011).…”
Section: Rheological Measurementssupporting
confidence: 84%
“…The decrease in gelling time as gelling agent concentration was increased is in agreement with work by Silva and Vasconcelos 27 on the gelation of sol-gel-derived silica with the use of HF catalysis. However, they found that the mean diameter of mesopores increased from 7 to 21 nm as HF concentration increased from 0.02 to 0.12 M, but the surface area decreased and the permeability increased.…”
Section: Gelling Agentsupporting
confidence: 90%
“…Glasses obtained by this method have been recommended for several applications such as bioactive materials; encapsulation of proteins, enzymes and biomolecules for controlled drug delivery; and, incorporation of nuclear waste. A new generation of ceramic materials with great structural properties has emerged with the sol-gel processing due to the possibility of manipulation and control of the nanoestructures 7,8 .…”
Section: Introductionmentioning
confidence: 99%